외부탄소 무주입 혐기-호기 생물막 공정에서 폐수 중 탄소, 질소의 동시제거 - 정수정; 이용운; 김덕진; 배상옥; 강창민 (한국수처리학회지, 19(6), 2011)
The combined anaerobic/aerobic(A/O) biofilm reactors filled with different types of media were operated under various conditions for simultaneous removal of carbon and nitrogen in wastewater. In this com bined system, the effect on nitrification was examined under operating conditions with various HRT(hydraulic retention time), influent COD_(Cr) and NH_4^+-N concentration. Effluent from aerobic reactor was recycled internally to anaerobic reactor with the ratio of 1.0 and 1.5. In anaerobic reactor, removal of organic matters in the influent wastewater and denitrification of NO_3-N in effluent recycled internally from aerobic reactor was successfully accomplished without any addition of external carbon sources. Removal ratio of COD_(Cr) and NO_3-N were above 96% and almost 97% in anaerobic reactor. To investigate the optimal operation conditions in aerobic reactor, NH4+-N concentration and HRT varied with 50~200 mg-N/L and 6~24h. Under the operating condition of HRT of 9h, the removal ratio of NH4+-N and COD_(Cr) was 96.2% and 81.7%, respectively in aerobic reactor. The removal ratio of NH_4^+-N was obtained as > 95% regardless of HRT and influent NH4+-N concentration in aerobic reactor. In conclusion, this combined system was well operated with no addition of external carbon source, and the competition between nitrifiers and heterotrophs was not an important factor. KCI Citation Count: 0